An Image-Based Mobile Health App for Postdrainage Monitoring: Usability Study - Liao, Chien-Hung; Wu, Yu-Tung; Cheng, Chi-Tung; Ooyang, Chun-Hsiang; Kang, Shih-Ching; Fu, Chih-Yuan; Hsu, Yu-Pao; Hsieh, Chi-Hsun; Chen, Chih-Chi (JMIR Publications, 2020)
BackgroundThe application of mobile health (mHealth) platforms to monitor recovery in the postdischarge period has increased in recent years. Despite widespread enthusiasm for mHealth, few studies have evaluated the usability and user experience of mHealth in patients with surgical drainage. ObjectiveOur objectives were to (1) develop an image-based smartphone app, SurgCare, for postdrainage monitoring and (2) determine the feasibility and clinical value of the use of SurgCare by patients with drainage. MethodsWe enrolled 80 patients with biliary or peritoneal drainage in this study. A total of 50 patients were assigned to the SurgCare group, who recorded drainage monitoring data with the smartphone app; and 30 patients who manually recorded the data were assigned to the conventional group. The patients continued to record data until drain removal. The primary aim was to validate feasibility for the user, which was defined as the proportion of patients using each element of the system. Moreover, the secondary aim was to evaluate the association of compliance with SurgCare and the occurrence of unexpected events. ResultsThe average submission duration was 14.98 days, and the overall daily submission rate was 84.2%. The average system usability scale was 83.7 (SD 3.5). This system met the definition of "definitely feasible" in 34 patients, "possibly feasible" in 10 patients, and "not feasible" in 3 patients. We found that the occurrence rates of complications in the SurgCare group and the conventional group were 6% and 26%, respectively, with statistically significant differences P=.03. The rate of unexpected hospital return was lower in the SurgCare group (6%) than in the conventional groups (26%) (P=.03). ConclusionsPatients can learn to use a smartphone app for postdischarge drainage monitoring with high levels of user satisfaction. We also identified a high degree of compliance with app-based drainage-recording design features, which is an aspect of mHealth that can improve surgical care.